Study Of Determinants Of Indonesian Inflation 2001-2021 - Febrianza Titania Rizky; Yuni Prihadi Utomo (Jurnal Ekonomi, 2024)
Inflation is a very crucial indicator for assessing macroeconomic conditions in Indonesia. Its influence is quite significant, it can even influence government policy, especially in macro matters. This research aims to measure the direction and magnitude of the influence of Bank Indonesia Interest Rates, Economic Growth, Money Supply, Exchange Rates, Government Budget Deficit, World Oil Prices, and Government Debt on Inflation in Indonesia during the 2001-2021 period. The data used is secondary data in the form of time series data from 2001-2021, obtained from official sources such as the Central Statistics Agency, Bank Indonesia, World Bank, as well as from the State Revenue and Expenditure Budget. For quantitative analysis, the multiple linear regression analysis method was used with Ordinary Least Square (OLS) as the tool. The results of the research show that Bank Indonesia Interest Rates and World Oil Prices have a positive effect on Inflation, while Economic Growth, Money Supply, Exchange Rates, Government Budget Deficit and Government Debt have no effect on Inflation in Indonesia in 2001-2021.